Does Affirmative Action Incentivize Schooling? Evidence from India - Khanna, Gaurav (The Review of Economics and Statistics, 2020)
Affirmative action raises the likelihood of getting into college or obtaining a government job for minority social groups in India. I find that minority group students are incentivized to stay in school longer in response to changes in future prospects. To identify causal relationships, I leverage variation in group eligibility, school age cohorts, and state-level intensity of implementation in difference-in-differences and regression discontinuity designs. These estimators consistently show that affirmative action incentivizes about 0.8 additional years of education for the average minority group student and 1.2 more years of education for a student from a marginal minority subgroup.